Reconnaissance of dioxin-like and estrogen-like toxicities in sediments of Taean, Korea-seven years after the Hebei Spirit oil spill. (February 2017) - Kim, Cheolmin; Lee, Inae; Jung, Dawoon; Hong, Seongjin; Khim, Jong Seong; Giesy, John P.; Yim, Un Hyuk; Shim, Won Joon; Choi, Kyungho
Abstract: Oil spills near the coastlines may damage marine and intertidal ecosystem. Constituents of the oil have been reported to cause toxic consequences mediated by aryl hydrocarbon receptor (AhR), and estrogen receptor (ER). In the present study, AhR– and ER–mediated toxicities of coastal sediments of Taean were investigated seven years after Hebei Spirit oil spill (HSOS). Sediment samples were collected on June and October 2014 from seven locations along the Taean coastline, where signs of oil spill were detected. Sediment samples were extracted in Soxhlet extractors and further processed through activated silica gels to separate into four fractions; F1 (saturate hydrocarbons), F2 (aromatic hydrocarbons), F3 (resins and polar compounds), and F4 (residues). ER–mediated and AhR–mediated potencies (% E2max and % TCDDmax ) of each fraction were determined using MVLN cells and H4IIE- luc cells, respectively. F2 and F3 fractions of Sinduri 1, Sinduri 2, and Sogeunri 1 samples showed greater AhR–mediated potencies (up to 107% TCDDmax ). Chemical analysis revealed that PAH components are correlated with AhR–binding activities. The % E2max results varied by sample: While there was no noticeable induction of ER–dependent responses (<45%), some aromatics fractions (F2) exhibited the highest ER–mediated responses. Compared with previous reports from the same sites, both AhR–mediated and ER–mediated potencies have decreased over time. Nevertheless, AhR–mediated potencies could be identified in the environmental samples even after 7 years of the incident. Therefore, possible ecosystem implications of these findings should be further investigated. Highlights: Dioxin-like toxicities were found in sediments affected by Hebei Spirit oil spill. Fractionized samples could not explain toxicities observed in whole extracts. Toxicity interactions of oil components are suspected in sediment samples of HSOS. Follow-up of mechanism-based bioassays combined with chemical analyses is required.